Preterm Birth and Low Birth Weight Following Icsi- Pregnancies - Demirol, Aygül; Güven, Süleyman; Gürgan, Timur (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To report preterm birth and low birth weight rate of intracytoplasmic sperm injection (ICSI) related pregnancies and to compare our data with literature findings. STUDY DESIGN: Three-hundred and eighty-nine pregnancies following controlled ovarian hyperstimulation and intracytoplasmic sperm injection were retrospectively evaluated. Patients’ characteristics including age, gestational age at delivery and birth weight were noted from special clinic files. Women with early pregnancy loss (bef ore 24 weeks) and those who underwent embryo reduction, and higher order multiple pregnancies (≥3 f etus) were excluded from the study. RESULTS: The mean female age of 31.61 ± 4.68 years at delivery with the average gestational age 36.65 ± 2.66 weeks. The preterm delivery rate in whole group was 29.00%, while the proportion of very preterm birth delivery was found to be 9.80%. The proportions of low birth weight and very low birth weight inf ant were 27.00% and 3.10%, respectively. The rates of preterm delivery, very preterm delivery, low birth weight and very low birth weight infant were significantly higher in twins than those in singletons. CONCLUSION: ICSI may be associated with an increased risk of preterm delivery and low birth weight and very low birth weight infant in singleton or twin pregnancies. However, the physiological mechanism for how this observation may be related to the procedures and drugs used in ICSI is not clear; infertility itself may probably play a role.